Pembentukan Karakter Disiplin Peserta Didik Melalui Pembiasaan Salat Berjamaah - Zein, Neng Zakiyah; Nugraha, Mulyawan Safwandy (Epistemic: Jurnal Ilmiah Pendidikan, 2022)
One of the efforts given by schools or madrasas to shape the character of students and have good morals, namely by making the habit of praying in congregation, both sunnah and obligatory prayers. Schools and madrasas provide opportunities for students to participate in praying together. Because with this habit, it is hoped that students will understand that prayer is a must or obligation for every Muslim, when they grow up it becomes a moral responsibility to carry it out. This study aims to determine and implement the implementation of the five daily congregational prayers in shaping the character of discipline. This type of research is a mix method, which is a combination of two forms of qualitative and quantitative approaches. The research location is in SMP and MTs Az-Zainiyyah Salabintana Sukabumi Regency, while the data collection techniques used include questionnaires, observations, interviews, and documentation. The population is 150 students of SMP MTs with a sample of 109 students. Based on a thorough data analysis on the implementation of five daily congregational prayers in shaping the character of the discipline, the researchers found several findings, namely: First, the condition of praying together five times in forming the character of discipline, in its implementation, students have not fully followed, but the program has been implemented, Second, The process of implementing the five daily congregational prayers in shaping the character of discipline is to provide motivation and direct examples by educators. Third, the inhibiting factor is the lack of self-awareness of students in improving prayer discipline at school, the supporting factor of the teacher being consistent in directing so that these obstacles can be resolved.